Hashimoto’s encephalopathy in a child treated with immunoglobulin therapy - Besnard, Stéphane; Beaume, Anne; Gil, Roger; Pluchon, Claudette; Oriot, Denis; Loiseau, Marie-Noelle (Journal of Pediatric Neurology, 2006)
This case report presents a 14-month follow-up of a case of Hashimoto’s encephalopathy (HE) treated with immunoglobulins for the first time in an 11-year-old adolescent. The diagnostic criteria were: (a) a drop in school performance and psychological withdrawal for several weeks, (b) an euthyroid state with a past medical history of autoimmune thyroiditis treated with thyroxin, (c) a first episode of tonic-clonic seizure with clinical and electroencephalographic (EEG) findings of encephalopathy, (d) a high serum concentration of antithyroglobulin and antithyroid peroxidase antibodies, (e) negative results of cerebrospinal fluid and blood studies for viral and bacterial infections. Her acute epileptic symptoms resolved with clonazepam. Immunoglobulin therapy (400 mg/kg/day for 5 days every 6 weeks) was given for 14 months. Her cognitive function was greatly improved but a light-to-mild cognitive deficit remained. An EEG performed at her 14-month follow-up showed a correlation with her cognitive improvement. We suggest that immunoglobulin can be used as a first-line therapy in HE to avoid side effects or relapses as has been described with long-term steroid therapy.
Keywords: Encephalopathy; thyroiditis disease; immunoglobulin